Guía didáctica: Técnicas de arteterapia en déficit de atención en sexto de básica de la EEB “Cacique Pintag” en el periodo lectivo 2021-2022. - Berrones Carrasco, Tania Lorena (2022)
ABSTRACT: This research aimed to determine the benefits of art therapy techniques in attention deficit disorder to create a didactic guide for sixth-grade students of the EEB "Cacique Pintag". The methodology was based on a qualitative approach, with a basic-ethnographic type design, by fundamental objective, by field location, and with an inductive-deductive method. The techniques used were observation and survey. The instruments were the observation form and the questionnaire. The population consisted of a total of 15 students, ten boys and five girls in the sixth year of primary education. The observation form was applied to the students, and the survey was to the two teachers who are in charge of the group; Among the most outstanding results, there is evidence of a group of students who present characteristics compatible with attention deficit, such as a high level of distractibility, they ignore the details of the work, on the other hand, the teachers do not apply strategies related to art therapy in the classroom, to increase the development of creativity, concentration, and expression of emotions mainly.